Necrotizing Enterocolitis in a 34-Week Premature Infant with COVID-19. (23rd December 2021) - Mannix, Mary K.; Blood, Danielle; Gomez-Duarte, Oscar G.; Davidson, Lauren
Abstract : Coronavirus disease 2019 (COVID-19) is a viral respiratory infection caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). While SARS-CoV-2 is a leading cause of morbidity and mortality in older adults, COVID-19 also affects newborn infants in nurseries and the Neonatal Intensive Care Units (NICUs). The majority of infected neonates are believed to acquire SARS-CoV-2 by horizontal transmission, and most of them have asymptomatic or mild symptomatic infections. In rare cases, infants with COVID-19 may have severe complications resulting in death. We report a case of COVID-19 in a premature neonate born at 34 weeks gestational age who presented with hypothermia and respiratory distress and subsequently developed clinical and radiological signs of necrotizing enterocolitis (NEC). The neonate received medical management, including antibiotics, suspension of gastric feeds, and intensive NICU support. The neonate's clinical condition improved without surgical intervention, and after 10 days of antibiotics and gradual reestablishment of gastric feeds, patient health condition returned to normal, and weeks later, he was discharged home. COVID-19 in infants is frequently asymptomatic or associated with mild disease, and in rare cases, it may be associated with severe gastrointestinal complications including NEC.